Bio-chemo-electro-mechanical modelling of the rapid movement of Mimosa pudica - Wang, Yifeng (2022)
A remarkable feature of Mimosa pudica is its ability to deform in response to certain external stimuli. Here, a two-dimensional transient bio-chemo-electro-mechanical model of the rapid movement of the main pulvinus of Mimosa pudica is developed. Based on the laws of mass and momentum conservation, poroelasticity, and representative volume elements, a novel fluid pressure equation is proposed to characterize the cell elasticity. Experiments were conducted to measure the time and amplitude of the rapid movement. After examinations with the published experiments, it is confirmed that the model can predict well the ionic concentrations, petiole bending angle, and membrane potential. The simulation analysis of the biophysical properties provides insights to biomechanics: the hydrostatic pressure in the lowest extensor decreases from 0.35 to 0.05 MPa at t = 0.00 to 3.00 s; fluid pressure increases from 0.00 to 0.11 MPa at t = 0.00 to 0.14 s; and the peak bending angle increases from 57.0° to 70.9° when the reflection coefficient is assigned as 0.10 to 0.20 in the model. The results highlight the biochemical actuation mechanism of the Mimosa pudica movement, and they confirm the importance of ionic and water transports for causing changes in osmotic and hydrostatic pressures.